Effects of Workplace-Related Factors on the Prevalence of Fibromyalgia among Israeli Kindergarten Teachers. (23rd October 2020) - Buskila, Yafa; Chen-Levi, Tamar; Buskila, Dan; Jacob, Giris; Ablin, Jacob J.
Abstract : Background . Fibromyalgia syndrome (FMS), a chronic widespread pain disorder, has been associated with various models of stress, including those that are workplace-related. In a previous study, we have documented the significantly increased prevalence of FMS among schoolteachers, as well as correlating symptoms with stressful workplace-related factors. In the current study, we have focused on the specific population of kindergarten teachers and attempted to document both the prevalence of FMS symptoms among this group and the association with stress and symptoms of posttrauma. Methods . All participants in the study were working as kindergarten teachers in Israel at the time of the study. Participants responded to a questionnaire documenting FMS symptom, which included the widespread pain index (WPI) and symptom severity scale (SSS), which together constitute the suggested American College of Rheumatology (ACR) FMS diagnostic criteria. Additional items on the questionnaire documented work motivation and performance, the occurrence of workplace-related stressful events, and the presence of posttraumatic symptoms. Results . 242 participants were recruited to the current study, including 239 (98.8%) females and 3 (1.2%) males. 62 individuals (25.6%) were found to fulfill ACR FMS criteria. Significant differences in work performance were found between teachers fulfilling FMS criteria compared with those not fulfilling criteria. Thus, FMS-positive teachers reported significantly higher rates of missing workdays, leaving work early, and a lower quality of interaction with children in the kindergarten and with peers and supervisors. Motivation to work was also significantly lower among these individuals. The widespread pain index (WPI) and symptom severity scale (SSS), which together constitute the components of the FMS diagnostic criteria, were positively correlated with both stress and posttraumatic symptoms. In addition, widespread pain, disordered sleep, difficulty with concentration, and other FMS symptoms were strongly correlated with many specific stressful factors at the workplace, including the number of children in the kindergarten, interaction with parents, lack of optimal physical conditions in the classrooms, and various demands on behalf of the educational system. Conclusion . FMS symptoms were found to be highly prevalent among Israeli kindergarten teachers, at a rate that greatly exceeds the prevalence in the general Israeli population. Stressful work-related events appear to be positively associated with the occurrence of FMS symptoms and may serve as triggers for their development. Healthcare professionals treating individuals engaged in this occupation should be vigilant for the occurrence of symptoms that are clinically associated with FMS and overlapping functional disorders.